WEBER, A. (2017). Matter & Desire. An Erotic Ecology, Vermont, Chelsea Green Publishing - Sobral Dorado, Montserrat (Daimon Revista Internacional de Filosofia, 2026)
Reseña de WEBER, A. (2017). Matter & Desire. An Erotic Ecology, Vermont, Chelsea Green Publish- ing